PROSPECTS FOR THE INTRODUCTION OF INNOVATIVE EDUCATIONAL TECHNOLOGIES IN MILITARY TRAINING - Bazarov Babur Oripovich Colonel; Dustjonov Farkhod Yaroshevich (American Journals Publishing, 2023)
In recent years, innovative educational technologies have gained a lot of attention in various fields, including the military one. This article examines the prospects and potential advantages of introducing innovative educational technologies into Army training programs. We study how these technologies can improve academic performance, improve the effectiveness of training procedures, and ultimately contribute to the development of highly qualified and flexible military personnel. Key areas of focus include virtual reality, augmented reality, gamification, and adaptive learning. Using the benefits of these technologies, armed forces around the world can revolutionize their educational programs and adapt to the ever-evolving challenges of Modern Warfare.